In Uzbekistan, the Possibility of Limited POPULATION of the Architecture of the Environment for the Organization - Isakova Mukaddas Badirovna (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
in this article in uzbekistan for persons with disabilities